Angiogenesis-Inflammation Cross Talk in Diabetic Retinopathy: Novel Insights From the Chick Embryo Chorioallantoic Membrane/Human Vitreous Platform - Rezzola, Sara; Loda, Alessandra; Corsini, Michela; Semeraro, Francesco; Annese, Tiziana; Presta, Marco; Ribatti, Domenico (Frontiers in Immunology, 2020)
Pathological angiogenesis of the retina is a key component of irreversible causes of blindness, as observed in proliferative diabetic retinopathy (PDR). The pathogenesis of PDR is complex and involves vascular, inflammatory, and neuronal mechanisms. Several structural and molecular alterations associated to PDR are related to the presence of inflammation that appears to play a non-redundant role in the neovascular response that characterizes the retina of PDR patients. Vascular endothelial growth factor (VEGF) blockers have evolved over time for the treatment of retinal neovascularization. However, several limitations to anti-VEGF interventions exist. Indeed, the production of other angiogenic factors and pro-inflammatory mediators may nullify and/or cause resistance to anti-VEGF therapies. Thus, appropriate experimental models are crucial for dissecting the mechanisms leading to retinal neovascularization and for the discovery of more efficacious anti-angiogenic/anti-inflammatory therapies for PDR patients. This review focuses on the tight cross talk between angiogenesis and inflammation during PDR and describe how the chick embryo chorioallantoic membrane (CAM) assay may represent a cost-effective and rapid in vivo tool for the study of the relationship between neovascular and inflammatory responses elicited by the vitreous humor of PDR patients and for the screening of novel therapeutic agents.